Studies on Characterization of Molecular Variability Using RAPD Markers in Rhizoctonia solani Isolated from Different Gerographical Regions of South India - Kumari, Krishna (International Journal of Applied Sciences and Biotechnology, 2015)
Molecular techniques have become reliable and are highly suitable tools for identifying pathogen species and for genetic variation. The molecular marker is a useful tool for assessing genetic variations. RAPD (Random Amplified Polymorphic DNA) markers have been used to characterize the numerous filamentous fungi collected from different fields of experimental mycology. Rhizoctonia solani is a plant pathogenic fungus which cause sheath blight in rice. Present work focused on polymorphic identification and characterization of Rhizoctonia solani isolate. Twenty eight samples were collected from different locations of South India and Punjab. Rhizoctonia solani (teleomorph: Thanatephorus cucumeris) were isolated and used polymorphic examination by molecular markers. Molecular analysis was done with OPC-5, OPC-2, OPA-8 and OPA-11primers and the variability of isolated fungus DNA, allowed the visualization of 265 polymorphic bonds with molecular weight ranging from 0.5kb to 20kb significant differences in RAPD profiles of 28 isolates of R. Solani were found with two primers OPC-5 and OPC-2. To analyze the resolving ability of these primers, cumulative RAPD profiles generated by the primers were analyzed by UPGMA. The dendrogram constructed using 265 polymorphic bonds obtained from 28 isolates with 5 primers was divided into 7 clusters. Based on these results it was concluded that there was a molecular variability among the isolates of R. solani was depicted.